Аналіз популярних рішень для побудови онлайн-спільноти випускників вишу - Березко, Олександр; Зуб, Христина (Видавництво Львівської політехніки, 2019)
Abstarct. In this paper the creation of an online social environment alumni is considered. Best practices of online systems for alumni management are analysed. Authors also present online comunity of Lviv Polytechnic National University alumni.
Keywords: випускники; університет; вищий навчальний заклад; веб-спільнота